Training Evaluation For Scientific-Based Electronic Module Development Using Sigil Software In MGMP Physics Teacher Surakarta - Shofi Hikmatuz Zahroh; Widha Sunarno; Pujayanto Pujayanto; Elvin Yusliana Ekawati; Ahmad Fauzi (LPPM UNS, 2025)
Professional and skilled teachers in e-learning-based instructions are needed to support the implementation of instructions that corresponds to the dynamics of the development of science and technology. For this reason, training is necessary for sustainability, both at school and outside of school. E-learning-related training requires no small amount of funds. That can be a problem in the professional development of the MGMP Physics teacher in Surakarta. To overcome these problems, the Physics Education Study Program FKIP UNS with the Physics Teacher Association (MGMP) Surakarta held training to develop scientific-based physics electronics modules using sigil software on several topics, that is (1) Elasticity and Hooke's Law (2) Temperature, Heat, and Heat Transfer, (3) Rotational Dynamics, (4) Static Fluids, (5) Dynamic Fluids, and (6) Kinetic Theory Gas. This training has four activities, that is (1) the explanation of the material about the nature of scientific-based electronic modules, (2) the introduction of the sigil and the procedures for its use, (3) training and practice to develop scientific-based electronic modules using Sigil software, and (4) discussion of the results of the electronic module development.